TOP-DOWN TO PARTISIPATIF: TRANSFORMASI KEBIJAKAN PEMBERDAYAAN INKULUSIF - Andi Susanto; Zaini Miftah (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Community empowerment is a crucial strategy in creating sustainable social change, especially amidst the challenges of social inequality and limited access. In the context of national development, community empowerment is a strategic component in improving welfare, as well as creating socio-economic independence at the grassroots level. However, various social policies that have been implemented so far are often top-down, less responsive to local needs, and have not fully empowered communities as subjects of development. This study aims to analyze and formulate the direction of social policy development that is oriented towards increasing community capacity and participation in various areas of life. A qualitative approach is used through literature studies, policy analysis and interviews with related stakeholders. The focus of the analysis is directed at three main aspects: social policy design, implementation of empowerment programs, and community participation in the decision-making process. This study also evaluates inter-institutional integration and synergy between the government, civil society organizations, and the private sector. The results of the study indicate that participatory social policies, responsive to local needs, and based on community assets are more effective in encouraging community independence. In addition, integration between government programs and civil society initiatives is key to creating an inclusive empowerment ecosystem. This study recommends the need for social policy reformulation through a multi-sector approach, strengthening local institutions, and developing success indicators based on long-term social impacts.